Family Health Strategy professionals facing Burnout syndrome: The disease of our time (Research, Society and Development, 2026)
Work occupies a central role in the lives of individuals, being a relevant factor for the formation of identity and social insertion. The well-being that comes from the balance between professional activity and other factors that make up what is understood as quality of life. However, these areas are not always in balance, which can make room for the individual's illness and for physical and mental illnesses. Burnout is defined as a psychological syndrome composed of three dimensions. Exhaustion thrills; depersonalization or cynicism; and low personal fulfillment and the development of a diagnostic scale. The work aims to investigate the Burnout disease. In addition, it seeks to understand how it affects individuals and discuss its implications for the health and quality of life of professionals. The methodology starts from scientific knowledge and it is a bibliographical research with a qualitative approach, in addition, it can be classified directly, as a basic research that aims to generate scientific knowledge and still being a descriptive research.